Suggestions for studying strategy process: A research note - van de ven, Andrew H. (Strategic Management Journal, 1992)
This paper makes three suggestions to researchers for studying strategy process. First, define the meaning of process. Process is often used in three ways in the literature: (1) a logic used to explain a causal relationship in a variance theory, (2) a category of concepts that refer to actions of individuals or organizations, and (3) a sequence of events that describe how things change over time. The second suggestion is to clarify the theory of process. An interdisciplinary literature review identifies four types of theories of process that can be drawn upon: life cycle, teleology, dialectics, and evolution. The third suggestion is to design research to observe strategy process in such a way that is consistent with one's definition and theory of process.